Pengembangan Website Desa Pelayanan Publik dan Informasi Warga dengan Menggunakan Metode Extreme Programming (XP) di Desa Bogoran, Kecamatan Kampak, Kabupaten Trenggalek (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Public services and information management in Bogoran Village, Kampak District, Trenggalek Regency, currently face obstacles due to reliance on conventional systems, including manual administrative processes and physical notice boards. This study aims to design and build a Public Service and Citizen Information Website in Bogoran Village using the Extreme Programming (XP) method, which includes four stages: Planning, Design, Coding, and Testing. The system was developed using the Laravel framework (PHP), MySQL database, and CSS for a responsive interface. Testing was conducted using Black Box Testing and User Acceptance Testing (UAT) involving 5 respondents. Black Box Testing results showed that all main features functioned as expected. UAT evaluation yielded an average feasibility percentage of 94.29%, categorized as very good. The system provides village information services, news publication, activity gallery, citizen complaint features, and WhatsApp notification integration, effectively improving public service effectiveness and information transparency in Bogoran Village.